Stalking von Psychiatern und Psychotherapeuten: Ergebnisse einer Onlinestudie = Stalking of psychiatrists and psychotherapists : results of an online survey - Praus, Peter; Riedel-Heller, Steffi Gerlinde; Dreßing, Harald (Der Nervenarzt, 2018)
Background Currently, there are clear indications that due to their exposed occupational position psychiatrists and psychotherapists are at a higher risk than the general public to become the victim of stalking by patients. Objectives This study investigated the frequency of stalking and its psychosocial impact among psychiatrists and psychotherapists in the Federal Republic of Germany. Methods Analysis of an online survey among members of the German Association for Psychiatry, Psychotherapy and Psychosomatics (DGPPN) from 23 September 2015 until 22 October 2015.ResultsOf the respondents 26.5% reported having been the victim of stalking. In more than a third of the reported cases the stalking was described as severely or very severely debilitating. The majority of the perpetrators suffered from psychotic or personality disorders. Male victims were significantly more frequently stalked by a female perpetrator. Approximately 1 in 10 stalking victims continued the treatment of the perpetrator. The majority of the stalking victims did not obtain substantial support from their employer. Conslusion The phenomenon of stalking within therapeutic relationships needs to be incorporated into the medical and psychotherapeutic professional training, e. g. by implementing specialized training courses and the systematic integration of this topic into clinical supervision. The institutional dealing with stalking by patients needs to optimized, e. g. by promptly transferring treatment of patients who stalk to other professionals and, where required, providing assistance in reporting stalking incidents to the police.
Gesehen am 18.09.2019
Online publiziert:13. März 2017